Transformational Leadership of Headteachers in Facilitating the Transformation of Pesantren-Based Schools - Baiq Nera Fazira; Ahmad Suyanto; Abdul Ghafir Ianatullah (At Tadbir: Islamic Education Management Journal, 2026)
This study was motivated by the importance of developing an educational model that focuses not only on academic aspects, but also on character building and religious values. The aim of this study is to analyse the role of the headteacher’s transformational leadership in transforming formal schools into pesantren-based institutions. A qualitative approach using a case study design was employed. The research was conducted at SMA Primaganda Jombang, involving the headteacher, teachers, students, and boarding school supervisors as informants. Data collection techniques included in-depth interviews, observation, and documentation, whilst data analysis utilised an interactive model comprising data reduction, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources and techniques. The results of the study indicate that the headteacher’s transformational leadership plays a crucial role in the success of boarding school-based school transformation. This role is evident through the headteacher’s exemplary conduct in religious life, the articulation of a vision that emphasises a balance between academic achievement and moral values, the promotion of values-based learning innovation, and a personalised approach to mentoring teachers and pupils. The transformation has taken place not only in structural aspects but also in changes to the school culture, improved discipline, and the development of pupils’ character. This study concludes that transformational leadership, which integrates managerial and spiritual dimensions, is a key factor in the success of boarding school-based education. Therefore, this leadership model can serve as an alternative in developing a more holistic and character-based education.